Implementation of lesson study through guided inquiry learning model to improve students' critical thinking - Isnawati, L Z; Caswita; Noer, S H (Journal of physics. Conference series, 2020)
This study aims to describe the application of guided inquiry models to improve students' critical thinking skills on the material of linear function class VIII A at SMP Negeri 1 Kota Agung. The type of research used in lesson study activities with guided inquiry consists of three stages of planning, doing, and seeing. Data collection techniques used in the form of interviews, tests, and documentation. The data analysis technique uses descriptive qualitative. The selection of material is based on the results of the midterm exams supported by the results of students' pretests. The subjects of this study were six students with low, medium and high skills. Students who have LS showed that the existence of critical thinking skills in the medium category with an N-Gain score of 0.4 to 0.45. Students who have MS have increased critical thinking skills in the medium category with an N-Gain score of 0.59 to 0.66. Students who have HS have increased critical thinking skills from the moderate to a high category with an N-Gain score of 0.68 to 0.76. The results of this study indicate that students' critical thinking skills in linear function material increased using Guided Inquiry through learning activities with low, medium or high skills.